2013
DOI: 10.1186/1756-9966-32-104
|View full text |Cite
|
Sign up to set email alerts
|

Association between polymorphisms in long non-coding RNA PRNCR1 in 8q24 and risk of colorectal cancer

Abstract: BackgroundGenome-wide association studies have identified that genetic variants in 8q24 confer susceptibility to colorectal cancer (CRC). Recently, a novel lncRNA (PRNCR1) that located in the 8q24 was discovered. Single nucleotide polymorphisms (SNPs) in the lncRNAs may influence the process of splicing and stability of mRNA conformation, resulting in the modification of its interacting partners. We hypothesized that SNPs in the lncRNA PRNCR1 may be related to the risk of CRC.MethodsWe conducted a case–control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 61 publications
1
71
2
2
Order By: Relevance
“…lncRNAs are involved in every aspect of cancer progression, such as initiation, cancer metastasis, and could function as oncogenes and tumor suppressors (22). PRNCR1 can promote the progression of prostate cancer, yet the function and molecular mechanism in CRC remain unknown (20,21,25,26).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…lncRNAs are involved in every aspect of cancer progression, such as initiation, cancer metastasis, and could function as oncogenes and tumor suppressors (22). PRNCR1 can promote the progression of prostate cancer, yet the function and molecular mechanism in CRC remain unknown (20,21,25,26).…”
Section: Discussionmentioning
confidence: 99%
“…The interactions of these overexpressed lncRNAs may potentially serve as important regulators in prostate cancer (21). For CRC, many researchers have reported that the crucial locus of 8q24 may contribute to susceptibility to CRC (22,23). It has been gradually recognized that aberration of PRNCR1 might be a biological signature of CRC, but its specific expression pattern related to CRC remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are untranslated transcripts longer than 200 nucleotides baring many of the structural characteristics of mRNAs, including a polyA tail, 5′-capping, and a promoter structure, but no conserved open reading frame [1][2][3][4][5][6]. Many lncRNAs are expressed at specific times and in specific tissues during development, and exhibit a variety of slicing patterns.…”
Section: Introductionmentioning
confidence: 99%
“…To date, certain studies have investigated the impact of PRNCR1 polymorphisms on the risk of various cancers, including prostate (26,(28)(29)(30), gastric (31,32) and colorectal cancer (33).…”
Section: Introductionmentioning
confidence: 99%